2022
DOI: 10.3390/life12060890
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kelulut Honey on Oestrus Cycle Regulation and Histomorphological Changes in Letrozole-Induced Polycystic Ovary Syndrome Rats: A Preliminary Study

Abstract: Polycystic ovary syndrome (PCOS) is a complex reproductive, metabolic, and endocrine disorder that affects women of reproductive age. Kelulut honey is stingless bee honey that possesses anti-inflammatory, anti-cancer, anti-diabetic, and potent antioxidative activities in most conditions. However, its value in improving PCOS remains to be elucidated. Thus, this preliminary study aimed to determine the effective dose of Kelulut honey in oestrus cycle regulation and ovarian histomorphological changes in letrozole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 57 publications
(77 reference statements)
5
11
0
Order By: Relevance
“…Furthermore, the combination of KH with metformin and clomiphene showed significant normalisation of the oestrus cycle. These results strengthen our previous finding which revealed oestrus cycle improvement in PCOS-induced rats treated with KH [ 28 ]. Previously, Tualang honey has been demonstrated to improve the bisphenol A-induced disruption of the oestrus cycle [ 64 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Furthermore, the combination of KH with metformin and clomiphene showed significant normalisation of the oestrus cycle. These results strengthen our previous finding which revealed oestrus cycle improvement in PCOS-induced rats treated with KH [ 28 ]. Previously, Tualang honey has been demonstrated to improve the bisphenol A-induced disruption of the oestrus cycle [ 64 ].…”
Section: Discussionsupporting
confidence: 92%
“…As demonstrated in our previous study [ 28 ], KH did not affect the blood glucose levels in PCOS rats. This agrees with previous observations which found that daily intake of KH for 30 days caused no changes in fasting blood glucose in patients who have impaired fasting blood glucose [ 60 ].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations